Potential Applications and Limitations of Artificial Intelligence in Remote Sensing Data Interpretation: A Case Study - Hossain, Ikram; Islam, Md Monirul; Martin, Md. Hasnat Hanjala (Control Systems and Optimization Letters, 2024)
This research aims to comprehensively review the applications and limitations of artificial intelligence (AI) in interpreting remote sensing data, highlighting its potential through a detailed case study. AI technologies, particularly machine learning and deep learning, have shown remarkable promise in enhancing the accuracy and efficiency of data interpretation tasks in remote sensing, such as anomaly detection, change detection, and land cover classification. AI-driven analysis has a lot of options because to remote sensing, which can gather massive amounts of environmental data via drones, satellites, and other aerial platforms. AI approaches, in particular machine learning and deep learning, have demonstrated potential to improve the precision and effectiveness of data interpretation tasks, including anomaly identification, change detection, and land cover classification. Nevertheless, the research also points to a number of drawbacks, including challenges related to data quality, the need for large labeled datasets, and the risk of model overfitting. Furthermore, the intricacy of AI models can occasionally result in a lack of transparency, which makes it challenging to understand and accept the outcomes. The case study emphasizes the necessity for a balanced strategy that makes use of the advantages of both AI and conventional techniques by highlighting both effective applications of AI in remote sensing and areas where traditional methods still perform better than AI. This research concludes that while AI holds significant potential for advancing remote sensing data interpretation, careful consideration of its limitations is crucial for its effective application in real-world scenarios.